Suillus triacicularis sp. nov., a new species associated with Pinus roxburghii from northwestern Himalayas, India - Reddy, Sudhakara M; Verma, Balwant (Phytotaxa, 2014)
A new Suillus species, Suillus triacicularis sp. nov., is reported from northwestern Himalayan region of India. This is the first report of any Suillus species found in ectomycorrhizal association with Pinus roxburghii in this region. Morphologically, the species is very close to Suillus granulatus but can be distinguished mainly by the yellow to reddish or orange-yellow pileus color at maturity and the absence of watery green context next to the tubes. Phylogenetic analysis of internal transcribed spacer region revealed that this species is distinct from other closely related species of Suillus. Field photographs of fresh sporocarps, microscopic line drawings, and a phylogenetic tree are provided along with the taxonomic details.